A peculiar adverse reaction to blue pigment tattoo. (2nd August 2020) - Tammaro, Antonella; Magri, Francesca; Chello, Camilla; Sernicola, Alvise; Luzi, Fabiola; De Marco, Gabriella; Raffa, Salvatore
Abstract: The practice of tattooing dates back to 5000 years ago and is currently constantly growing. The most common pigment associated with tattoo complications is the red one. Another pigment, which could be associated with adverse reactions, even if less frequently than red, is blue. Traditionally, blue pigment contains cobalt, which causes allergic reactions. Here, we report a case of blue pigment granulomatous reaction in a 37‐year‐old male patient.